On Mochizuki-Trooshin Theorem for Sturm-Liouville Operators - ADALAR, İbrahim (Cumhuriyet Science Journal, 2019)
In this paper, the inverse spectral problems of Sturm-Liouville operators are considered. Some new uniqueness theorems and analogies of the Mochizuki-Trooshin Theorem are proved. 2010 Mathematics Subject Classification. Primary 34A55, 34B24; Secondary 34L05. Bu makalede, Sturm-Liouville operatörlerinin ters spektral problemleri ele alınmıştır. Bazı yeni teklik teoremleri ve Mochizuki-Trooshin teoreminin benzetimleri ispatlanmıştır.